Individuo y sociedad en Th. W. Adorno: tensiones y mediaciones entre teoría de la sociedad y psicoanálisis = Individual and Society by Th. W. Adorno: tensions and mediations between social theory and psychoanalysis - Zamora, José António (Veritas)
This article analyzes the relationship between individual and society in Theodor W. Adorno. For this, it focuses on the tensions and mediations between the theory of society and psychoanalysis. Its starting point is the concrete historical horizon of the link that unites both: the conjunction of crisis and integration. Then, it presents the social constitution of subjectivity from the perspective of critical theory, the psychic-libidinal economy as the psychosocial matrix of this constitution, the thesis of the debilitation of the individual in an authoritarian monopolistic capitalism and its expression in the authoritarian personality and the wounded narcissism. Finally, it presents the historical limits of the neurotic subject and oedipal model and the elements of a possible update of the contributions of a psychoanalytic social psychology